Aligning TVET Curriculum with Fourth Industrial Revolution Skills for the Food Services Industry: A Mixed Methods Approach - Amiron, Evarina; Abdul Latib, Azlan (Journal of Technical Education and Training, 2024)
This paper studies factors influencing skills acquisition when using Fourth Industrial Revolution (4IR) technologies in a Food Services working environment. The scope of this study is at dine-in restaurants in four Malaysian states representing the Northern, Central, and Southern zones. A pragmatic paradigm and mixed methods approach were applied in the research design allowing the supplementing of data between the qualitative and quantitative phases. The sequential exploratory mixed methods approach was applied allowing input from the interview’s thematic analysis to provide context to the survey instrument’s development. This approach Input was gathered from different sample groups such as restaurant managers (9 interview participants), restaurant workers (93 survey respondents), and skills development collaborators (19 survey respondents). The data were analysed through thematic analysis, PLS-SEM, and the Fuzzy Delphi Method. Thematic analysis interpreted interview data, PLS-SEM identified relationships among factors, and the Fuzzy Delphi Method captured expert consensus on 4IR skills. Findings revealed that the significant factors for skills acquisition when using 4IR technologies are Compatibility, Trialability, Social Systems, and Relative Advantage, based on the Diffusion of Innovation theory. These factors were then aligned with the Technological-Organizational-Environmental theory’s framework to guide the integration of 4IR skills into the current TVET curriculum.